2007
DOI: 10.4049/jimmunol.178.12.7923
|View full text |Cite
|
Sign up to set email alerts
|

Paratope Plasticity in Diverse Modes Facilitates Molecular Mimicry in Antibody Response

Abstract: The immune response against methyl-α-d-mannopyranoside mimicking 12-mer peptide (DVFYPYPYASGS) was analyzed at the molecular level towards understanding the equivalence of these otherwise disparate Ags. The Ab 7C4 recognized the immunizing peptide and its mimicking carbohydrate Ag with comparable affinities. Thermodynamic analyses of the binding interactions of both molecules suggested that the mAb 7C4 paratope lacks substantial conformational flexibility, an obvious possibility for facilitating binding to che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Structural evidence has suggested that Abs with high affinity manifest a ''lock and key'' type of binding, involving a higher amount of polar and charged interactions [16][17][18]22] that contribute to the rigidity of the Ag-binding site and to a higher binding energy for the AbAg interaction [16,18,22,23]. By contrast, more crossreactive Abs show fewer electrostatic contributions to Ab-Ag binding and an increase in hydrophobicity [24], thus allowing for greater molecular flexibility [25]. Flexible areas have more intermolecular interactions, via polar and charged residues, in comparison to the rigid regions [17,18].…”
Section: Reviewmentioning
confidence: 91%
“…Structural evidence has suggested that Abs with high affinity manifest a ''lock and key'' type of binding, involving a higher amount of polar and charged interactions [16][17][18]22] that contribute to the rigidity of the Ag-binding site and to a higher binding energy for the AbAg interaction [16,18,22,23]. By contrast, more crossreactive Abs show fewer electrostatic contributions to Ab-Ag binding and an increase in hydrophobicity [24], thus allowing for greater molecular flexibility [25]. Flexible areas have more intermolecular interactions, via polar and charged residues, in comparison to the rigid regions [17,18].…”
Section: Reviewmentioning
confidence: 91%
“…Using OptMAVEn, we, de novo, designed single‐chain antibodies (scFvs) against the dodecapeptide antigen DVFYPYPYASGS. The dodecapeptide with its Tyr‐Pro‐Tyr motif mimics the carbohydrate methyl α‐ D ‐mannopyranoside, which has been studied extensively since it is the recognition target of lectin concanavalin A (con A) and mAb‐2D10 (Krishnan et al, ; Tapryal et al, ). Association with the two antigens (dodecapeptide and methyl α‐ D ‐mannopyranoside) occurs at different sites for con A.…”
Section: Introductionmentioning
confidence: 99%
“…Because little is known about the chemical nature of important antigens, that is, whether they are proteins, carbohydrates, or lipids, peptide phage display technology was used to identify ligands for CLL mAbs. This approach has successfully identified mimetic epitopes of proteins, 23 carbohydrates, [24][25][26] lipids, 27 and DNA. 28 Our data indicate that phage display is a feasible technique to identify and characterize ligands binding to M-CLL and U-CLL.…”
Section: Introductionmentioning
confidence: 99%